Die Europäisierung des Privatrechts und die Rechtsvergleichung. Vortrag, gehalten vor der Juristischen Gesellschaft zu Berlin am 15. Juni 2005 - Zimmermann, Reinhard (Schriftenreihe der Juristischen Gesellschaft zu Berlin, 2006)
Lecture held before the Judicial Society in Berlin on June 15, 2005, on the subject of the Europization of private law as a function of and challenge for comparative law.